The bank lending survey for the euro area - Jesper Berg; Annalisa Ferrando; Gabe de Bondt; Silvia Scopel (European Central Bank (ECB), 2005)
This occasional paper explains why the bank lending survey was developed by the ECB and describes its main features. It discusses the importance of credit developments for both the economy and the functioning of monetary policy, and further clarifies why the survey was introduced. Furthermore, the paper demonstrates that the value added of implementing a bank lending survey for the euro area lies in particular in the way it provides greater insight into developments in credit standards, non-interest rate credit conditions and terms, the risk perception of banks and the willingness of banks to lend. Credit standards are the internal guidelines or criteria of a bank which reflect the bank's loan policy. The terms and conditions of a loan refer to the specific obligations agreed upon by the lender and the borrower. This occasional paper also considers similar surveys conducted by the Federal Reserve System in the US and by the Bank of Japan.
Keywords: E43; E51; G21; 330; Survey; Banks; Credit Standards; Credit Markets; European Central Bank; Federal Reserve; Bank of Japan; Kredit; Kreditgeschäft; Eurozone; EU-Staaten